2007
DOI: 10.1097/mao.0b013e31815a8433
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Changes of Contralateral Human Temporal Bone in Unilateral Ménière's Disease

Abstract: The contralateral inner ear in patients with unilateral Ménière's disease has significantly more damage compared with inner ears of normal controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…Moreover, when compared to normal controls, there was also significant atrophy in the stria vascularis in the contralateral ear, while the mean loss of inner and outer hair cells at all turns of the cochlea was significantly higher. The number of spiral ganglion cells was also significantly reduced and did not differ from that in the symptomatic ear [Kariya et al, 2007]. This correlated well with the audiometry findings, as a clear correlation between hearing levels in both ears has been found in the quiescent phase as well as during the fluctuations [Takumida et al, 2006].…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, when compared to normal controls, there was also significant atrophy in the stria vascularis in the contralateral ear, while the mean loss of inner and outer hair cells at all turns of the cochlea was significantly higher. The number of spiral ganglion cells was also significantly reduced and did not differ from that in the symptomatic ear [Kariya et al, 2007]. This correlated well with the audiometry findings, as a clear correlation between hearing levels in both ears has been found in the quiescent phase as well as during the fluctuations [Takumida et al, 2006].…”
Section: Discussionsupporting
confidence: 76%
“…It must be stressed that even in the absence of clinical signs and symptoms of bilaterality, histopathologic changes, such as loss of cochlear hair cells and spiral ganglion cells, degeneration of stria vascularis, and reduced density of fibrocytes in the spiral ligament, have been found in the asymptomatic contralateral ear of the unilateral MD patients (28). The limited number of the patients examined bilaterally in the present investigation does not enable conclusive considerations.…”
Section: Discussionmentioning
confidence: 91%
“…6). Other findings with unclear significance have also been reported in temporal bones from donors who had Meniere’s disease, including blockage of the ductus reuniens 16,20,28 (Figs. 7 and 8) and Cupulolithiasis 16,28 (Fig.…”
Section: Histopathology and Pathophysiologymentioning
confidence: 81%
“…4). 20–23 However, Kariya et al 20 reported these findings: bilateral ischemia of the stria vascularis (Fig. 5); fibrous tissue proliferation within the vestibule; and focal loss of neurons, as well as degeneration of the dendrites, in the upper middle and apical turns of the cochlea (Fig.…”
Section: Histopathology and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation